Genome insight and probiotic potential of three novel species of the genus Corynebacterium - Shamsuzzaman, Md; Dahal, Ram Hari; Kim, Shukho; Kim, Jungmin (Frontiers in Microbiology, 2023)
Three bacterial strains, B5-R-101T, TA-R-1T, and BL-R-1T, were isolated from the faeces of a healthy Korean individual. Cells of these strains were Gram-stain-positive, facultatively anaerobic, oxidase-negative, catalase-positive, rod-shaped, and non-motile. They were able to grow within a temperature range of 10–42 °C (optimum, 32–37 °C), at a pH range of 2.0–10.0 (optimum, pH 5.5–8.0) and at NaCl concentration of 0.5–10.5 % (w/v). All the three strains exhibited DPPH (2,2-Diphenyl-1-picrylhydrazyl) radical scavenging activities ranging from 58 ± 1.62% to 79 ± 1.46% (% inhibition). These strains survived in lower pH (2.0) and in 0.3% bile salt concentration for 4 h. They did not show hemolytic activity and exhibited antimicrobial activity against pathogenic bacteria such as Escherichia coli, Acinetobacter baumannii, Staphylococcus aureus, and Salmonella enterica. The genomic analysis presented no significant concerns regarding antibiotic resistance or virulence gene content, indicating these strains could be potential probiotic candidates. Phylogenetic analysis showed that they belonged to the genus Corynebacterium, with 98.5–99.0% 16S rRNA gene sequence similarities to other members of the genus. Their major polar lipids were diphosphatidylglycerol and phosphatidylglycerol. The abundant cellular fatty acids were C16:0, C18:1ω9c, and anteiso-C19:0. Genomic analysis of these isolates revealed the presence of genes necessary for their survival and growth in the gut environment, such as multi-subunit ATPases, stress response genes, extracellular polymeric substance biosynthesis genes, and antibacterial genes. Furthermore, the genome of each strain possessed biosynthetic gene clusters with antioxidant and antimicrobial potentials, including terpenes, saccharides, polyketides, post-translationally modified peptides (RIPPs), and non-ribosomal peptides (NRPs). In silico DNA–DNA hybridization (dDDH) and average nucleotide identity (ANI) values were lower than the thresholds to distinguish novel species. Based on phenotypic, genomic, phylogenomic, and phylogenetic analysis, these potential probiotic strains represent novel species within the genus Corynebacterium, for which the names Corynebacterium intestinale sp. nov. (type strain B5-R-101T = CGMCC 1.19408T = KCTC 49761T), Corynebacterium stercoris sp. nov. (type strain TA-R-1T = CGMCC 1.60014T = KCTC 49742T), and Corynebacterium faecium sp. nov. (type strain BL-R-1T = KCTC 49735T = TBRC 17331T) are proposed.